The Lived Experience of Gynecologic Cancer Survivors in Taiwan. Issue 6 (December 2017) - Tsai, Li-Yun; Wang, Kung-Liahng; Liang, Shu-Yuan; Tsai, Jung-Mei; Tsay, Shiow-Luan
ABSTRACT: Background: Although it is now possible to achieve permanent remission in a large percentage of gynecologic cancer (GC) cases, many GC patients in remission experience side effects or complications that influence their physical function and family relationships. Compared with other types of cancer patients, survivors of GC face greater challenges in terms of physical and psychological adaptations, and many of these do not receive sufficient assistance. An in-depth understanding of the lived experiences and demands of GC survivors is key to constructing comprehensive related healthcare services. Purpose: The aim of this study was to understand the lived experience of GC survivors in Taiwan to help their return to a healthy life. Methods: This was a phenomenological study. Twenty-three survivors of GC participated in semistructured interviews that were held in a private environment. The transcripts were based on synchronous recordings from the interviews. Giorgi's phenomenology analysis was adopted for data analysis. Results: Three themes with six subthemes were extracted from the data, including (a) the inner struggle of living with cancer and recurrence: repeatedly exploring the causes of cancer and treatment and facing a fear of cancer recurrence, (b) the interpretation and adjustment to cancer treatment: filled with fluctuating physical and mental distress and working to adopt a different perspective, and (c) the long passage of finding a desirable lifestyle: adjusting to long-term coexistence with side effects and realizing the strength of society, body, and mind. Conclusions/Implications for Practice: The journey of rehabilitation for GC survivors is very long. The participants in this study faced different respective challenges during the diagnosis, treatment, and adjustment phases. Conventional disease-oriented medical care cannot satisfy the requirements of cancer patients because of patient-decentralized services. Our results indicate that GC survivors face diverse problems, both physically and mentally. Healthcare professionals should work to facilitate the psychological adjustment of cancer survivors and provide timely professional advice in combination with social resources. These results may serve as a reference for cancer care professionals who are navigating healthcare services.